Acceptability and efficacy of a gel hypotonic oral rehydration solution in children with acute gastroenteritis. Issue 5 (May 2015) - Passariello, Annalisa; Nocerino, Rita; Terrin, Gianluca; Cecere, Gaetano; De Marco, Giulio; Micillo, Maria; Pezzella, Vincenza; Cosenza, Linda; Malamisura, Monica; Maddalena, Ylenia; Canani, Roberto Berni
Abstract : Objective: Oral rehydration solution remains the mainstay of acute gastroenteritis therapy. The aim of this study was to investigate the acceptability of a new zinc-containing hypotonic super-oral rehydration solution (ORS) in a gel formulation and its efficacy in reducing the duration and severity of diarrhea in children. Methods: This was a randomized-controlled trial of children (5–36 months of age) observed for diarrhea lasting less than 24 h. Children were randomized to receive standard hypotonic ORS (group 1) or a gel hypotonic super-ORS containing zinc (group 2). The main study outcome was ORS intake in the first 24 h. ORS intake at 4 h, rate of diarrhea resolution at 72 h of treatment, total duration and severity of diarrhea, hospitalization, and adverse effects were also evaluated. Results: Eighty-three children were enrolled (group 1: 40; group 2: 43). The amount of ORS consumed at 24 h was significantly higher in group 2 than in group 1. A similar result was observed at 4 h. The number of children who refused ORS (<10 ml/kg/day) was lower in group 2 versus group 1 ( P =0.001). The number of children presenting diarrhea after 72 h of treatment was lower in group 2 versus group 1 ( P =0.028). Also, the mean duration of diarrhea was shorter in group 2 than in group 1 ( P =0.001). The hypotonic super-ORS containing zinc in a gel formulation had a positive effect on the severity of diarrhea. No patient required hospitalization. No adverse events were observed in either of the two study groups. Conclusion: The new zinc-containing hypotonic super-ORS in a gel formulation is effective in the management of childhood acute gastroenteritis.